Principal Leadership Strategies for Enhancing Elementary School Quality: Comparative Case Studies of Two Urban Schools in Indonesia - Dewi Komarasari; Okke Rosmaladewi (UIN Sunan Gunung Djati Bandung, 2026)
In a school environment, principal leadership can impact learning. A leader must be dedicated to advancing the school and raising learning standards in the institution they lead. The principal's role has a significant impact on how education is developed and improved. Focusing on SDN Bunut and SDN Kabandungan in Sukabumi City, this study attempts to characterize and examine principals' management practices in improving learning standards at the elementary school level. This study focuses on how principals plan, implement, and evaluate initiatives to improve educational quality. A qualitative research strategy, combined with a case study methodology and a multi-site research design, was used. In-depth interviews, documentation studies, and observations were used as data collection methods. Based on the research findings, principals at both schools can strategically improve learning standards by promoting a collaborative work environment, encouraging teachers to be professional, making optimal use of available school resources, and enlisting the support of parents and the community to support educational initiatives. The implementation of quality improvement management is also hampered by various issues, including limited budgets, inadequate infrastructure, and differences in teacher skills. On the other hand, data-driven, adaptive, and participatory leadership techniques can be more effective in encouraging the achievement of learning objectives. The findings of this study indicate that improving teaching standards at the elementary school level will largely depend on teacher quality, including the leadership of communicative, visionary, and sensitive principals.